2018
DOI: 10.1111/iej.12961
|View full text |Cite
|
Sign up to set email alerts
|

Shaping ability of BioRace, ProTaper NEXT and Genius nickel‐titanium instruments in curved canals of mandibular molars: a MicroCT study

Abstract: The shaping ability of the BR, PTN and GN NiTi file systems was equally effective. All instrumentation systems prepared curved root canal systems with no evidence of undesirable changes in 3D parameters or significant shaping errors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
2
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 34 publications
2
33
2
6
Order By: Relevance
“…The comparison between groups displayed significant differences regarding changes in 3D parameters after preparation, and the hybrid GN system demonstrated a superior shaping ability compared to the reciprocating WO system. Previous findings revealed that the shaping ability of the hybrid GN instruments is not superior to rotary endodontic instruments [7]. However, no studies have compared the efficiency of these instruments to reciprocating systems.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…The comparison between groups displayed significant differences regarding changes in 3D parameters after preparation, and the hybrid GN system demonstrated a superior shaping ability compared to the reciprocating WO system. Previous findings revealed that the shaping ability of the hybrid GN instruments is not superior to rotary endodontic instruments [7]. However, no studies have compared the efficiency of these instruments to reciprocating systems.…”
Section: Discussionmentioning
confidence: 93%
“…The preservation of the original root canal configuration and lack of procedural errors, such as root canal transportation, and avoidance of instrument separation, is directly related to the higher success rates of endodontic treatment and survival of the endodontically treated teeth [20]. During the last decade, the µCT imaging has been the most widely used method to precisely quantify and qualify many 3D parameters of the root canals after cleaning and shaping procedures [7,12,21]. It has been shown that extracting natural teeth is superior to simulating root canals for testing the shaping abilities of endodontic instruments, as they represent more realistic clinical conditions [22,23].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations